2005
DOI: 10.1079/sum2005356
|View full text |Cite
|
Sign up to set email alerts
|

Response of soyabean (<I>Glycine max</I> Mer.) to wheat straw mulching in different cropping seasons

Abstract: The favoured temperature range for soyabean seed germination is 25 -30 8C and the crop is sensitive to water stress. In northern India, the crop is sown in the hot-dry months of May -June. Straw mulching can alter the soil's hydrothermal regime by lowering the temperature and reducing evaporation losses. A field experiment was conducted from 1999 to 2002 at the Research Farm of Punjab Agricultural University, Ludhiana on a loamy sand soil to evaluate the effect of wheat straw mulch on soil temperature, soyabea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 7 publications
5
23
0
1
Order By: Relevance
“…The soil moisture conserved with mulch was 4.5, 12.7 and 17.9 mm in IW/Pan-E ¼ 0.8, 0.6 and 0.4, respectively. Improvement in soil moisture storage and lowering of soil temperature with straw mulching is in agreement with the findings of Schonbeck and Evanylo (1998), Aulakh and Sur (1999), Agele et al (2000), Ossom et al (2003), and Sekhon et al (2005).…”
Section: Soil Temperaturesupporting
confidence: 91%
See 1 more Smart Citation
“…The soil moisture conserved with mulch was 4.5, 12.7 and 17.9 mm in IW/Pan-E ¼ 0.8, 0.6 and 0.4, respectively. Improvement in soil moisture storage and lowering of soil temperature with straw mulching is in agreement with the findings of Schonbeck and Evanylo (1998), Aulakh and Sur (1999), Agele et al (2000), Ossom et al (2003), and Sekhon et al (2005).…”
Section: Soil Temperaturesupporting
confidence: 91%
“…Our previous studies on soybean also reported greater advantage of soybean to wheat straw mulch under high temperature, low rainfall environments (Sekhon et al 2005). Nijamudeen and Dharamasena (2002) also reported a 32% increase in yield and 28% lower water consumption in chilli due to the application of mulch.…”
Section: Introductionmentioning
confidence: 86%
“…subtropical and semi-arid) with temperature exceeding the optimum for soybean growth, early application of straw mulch to suppress soil temperature can be an advantage (e.g. Sekhon et al, 2005;Lipiec et al, 2013). Therefore, reduction in soil temperature by mulch may have a positive or negative effect on soybean growth, depending on the climate and associated soil temperature during early growth.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, we not only found that chlorophyll content was the highest in M4 and the lowest in M0, but that the differences among M2, M3, M4, M5, and M6 were not significant; this indicates that straw mulching could significantly increase maize chlorophyll content when compared to the treatment without mulching, and the effects of straw mulching would decrease when the straw mulching level increased to a certain level. Sekhon et al (2005) Values are means ± SD (n = 5). Means followed by different letters in the same column indicate a significant difference (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%